Analysis of the failure of implementation of Good Corporate Governance (GCG): Case study of PT Bumi Asih Jaya - Muslimin, Muhammad Akhul (Maliki Interdisciplinary Journal, 2025)
This study discusses the importance of implementing Good Corporate Governance (GCG) in maintaining the sustainability and integrity of the company, especially in the insurance industry. This study uses a descriptive-analytical approach based on secondary data obtained through literature study and online exploration. The main focus is on the failure of PT Asuransi Jiwa Bumi Asih Jaya as a result of the weak implementation of GCG principles, such as transparency, accountability, and risk management. By examining GCG theories, such as Agency Theory, Stakeholder Theory, Resource Dependency Theory, and Stewardship Theory, this study shows that governance failures not only resulted in the company's collapse, but also harmed thousands of policyholders. The results of the study confirm that supervision and consistent implementation of GCG are crucial requirements to maintain public trust and ensure consumer protection in the financial sector.